2014
DOI: 10.1890/es13-00331.1
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic predictors of ecosystem engineering traits of the dune building grass, Ammophila breviligulata

Abstract: Citation: Emery, S. M., and J. A. Rudgers. 2014. Biotic and abiotic predictors of ecosystem engineering traits of the dune building grass, Ammophila breviligulata. Ecosphere 5(7):87. http://dx.doi.org/10.1890/ES13-00331.1Abstract. Ecosystem engineers are species that fundamentally influence their community and ecosystem by creating or altering the physical structure of habitats. However, the function of ecosystem engineers is variable and can depend on abiotic and biotic factors. In this study, we characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 71 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…In addition, if under warming conditions A. breviligulata experiences a range shift to the north, as appears to be occurring with U. paniculata, changes in grass dominance and foredune morphology could make coastal regions more vulnerable to erosion and overtopping. Interestingly, in an observational study in the Great Lakes region, Emery and Rudgers [41] found that A. breviligulata plants were taller at lower latitudes but shoot densities did not vary with any climate variables. Thus, while shifts in dune grass species' ranges are important to document, focusing on the physiological and morphological changes of dune grasses with changing climate is likely to be equally important to predicting foredune landscapes in the future.…”
Section: Dune Grass Distributions and The Consequences For Foredune Gmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, if under warming conditions A. breviligulata experiences a range shift to the north, as appears to be occurring with U. paniculata, changes in grass dominance and foredune morphology could make coastal regions more vulnerable to erosion and overtopping. Interestingly, in an observational study in the Great Lakes region, Emery and Rudgers [41] found that A. breviligulata plants were taller at lower latitudes but shoot densities did not vary with any climate variables. Thus, while shifts in dune grass species' ranges are important to document, focusing on the physiological and morphological changes of dune grasses with changing climate is likely to be equally important to predicting foredune landscapes in the future.…”
Section: Dune Grass Distributions and The Consequences For Foredune Gmentioning
confidence: 98%
“…These large-scale distributional differences are associated with physiological responses to climate. Ammophila breviligulata is a C 3 grass that prefers temperate climates, with plants susceptible to mortality above 35 • C [40,41]. Uniola paniculata is a C 4 grass that prefers warmer climates and appears to be limited by cold winter temperatures [42,43].…”
Section: Dune Grass Distributions and The Consequences For Foredune Gmentioning
confidence: 99%
“…Connections between ramets are separated by long internodes resulting in widely spaced ramets that influence dune morphology (Ye et al 2006;Emery and Rudgers 2013;Brantley et al 2014). It is a dominant pioneer species of foredune habitat that once established, plays an important role capturing sand and creating tall foredunes (Emery and Rudgers 2014). Ammophila breviligulata can withstand very high rates of sand burial, up to 1 m of sand per year, which significantly contributes to foredune formation (Maun and Lapierre 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It hosts an undescribed species of Epichloë (Emery et al ). The most commonly used nursery stocks for dune restoration material have 100% endophyte prevalence, whereas the prevalence of Epichloë in Great Lakes A. breviligulata populations is more variable (∼22% of Great Lakes populations were symbiotic, Emery et al , Emery and Rudgers ). To assess the interactive effects of above‐ground plant symbionts and climate on decomposition in a native ecosystem, we manipulated Epichloë sp.…”
mentioning
confidence: 99%